On the Road to the Membership of the European Communities. Political, Economic and Social Changes in Greece, Spain, Portugal discussed in the “Polityka” weekly magazine (1981-1987) - Barabasz, Adam (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2022)
The main aim of the article is to present the views and opinions of the editors of the Polityka weekly on the extension of the European integration process to Greece, Spain and Portugal in 1981–1987. The author’s intention is to present reactions of journalists writing for the opinion-forming weekly in Poland to the political, economic and social changes taking place in the southern European states. The article uses the historical method and the analysis of sources and press articles. The following methods also proved to be useful: institutional and legal, comparative, decision-making and behavioral.

Zasadniczym celem artykułu jest przedstawienie poglądów i opinii redakcji tygodnika “Polityka” na rozszerzenie procesu integracji europejskiej o Grecję, Hiszpanię i Portugalię w latach 1981–1987. Zamierzeniem autora jest przybliżenie reakcji publicystów opiniotwórczego tygodnika w Polsce na przemiany polityczne, ekonomiczne i społeczne zachodzące w krajach południa Europy. W artykule zastosowano metodę historyczną, metodę analizy źródeł i zawartości prasy. Przydatne okazały się również metody: instytucjonalno-prawna, porównawcza, decyzyjna oraz behawioralna.
Na drodze do członkostwa we Wspólnotach Europejskich. Polityczne, ekonomiczne i społeczne przemiany w Grecji, Hiszpanii, Portugalii na łamach tygodnika “Polityka” (1981-1987)
Keywords: European integration; PRL; NATO; EEC; integracja europejska